2015
DOI: 10.1182/blood.v126.23.2747.2747
|View full text |Cite
|
Sign up to set email alerts
|

CD30/CD16A Tandab AFM13-Induced Target Cell Lysis By NK-Cells Is Enhanced By CD137 Co-Stimulation and Blocking PD-1

Abstract: Introduction: AFM13 is a CD30/CD16A bispecific tetravalent TandAb antibody that recruits and activates NK-cells by specific binding to CD16A for targeted lysis of CD30+ tumor cells. Given promising clinical activity and safety profile of AFM13 and proof-of-mechanism demonstrating dependence on the immune response, potential synergy of AFM13 and checkpoint modulators was evaluated. Methods: Efficacy of AFM13 alone or in combination with anti-CTLA-4, anti-PD-1, or anti-CD137 antibodies was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Once the receptor is bound to the cognate antigen, the cytoplasmic chain events are triggered [ 37 ]. One of the primary sites for the phosphorylation of CD3ζ required cytoplasmic immunoreceptor tyrosine-based activation motifs (ITAMs) [ 38 , 39 ]. Signal transduction requires the phosphorylation of these ITAMs by the Src family tyrosine kinases Lck and/or Fyn.…”
Section: Architecture Of Carsmentioning
confidence: 99%
“…Once the receptor is bound to the cognate antigen, the cytoplasmic chain events are triggered [ 37 ]. One of the primary sites for the phosphorylation of CD3ζ required cytoplasmic immunoreceptor tyrosine-based activation motifs (ITAMs) [ 38 , 39 ]. Signal transduction requires the phosphorylation of these ITAMs by the Src family tyrosine kinases Lck and/or Fyn.…”
Section: Architecture Of Carsmentioning
confidence: 99%
“…This led to enhanced cytotoxic killing and cytokine production against various CD19-expressing B-cell lines [101]. A CD33xCD16 BiKE was developed against AML and demonstrated that killing by NK cells could be achieved [102]. During the activation of NK cells, gradual loss of CD16 and CD62L was observed.…”
Section: Novel Bispecific Antibodies or Single-chain Variable Fragment Targeting Nk Cellsmentioning
confidence: 99%